Komodifikasi Dakwah Digital: Personal Branding Dai dan Negosiasi Otoritas Keagamaan melalui Interaksi Audiens di Media Sosial - Nawaf, Azmi (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2025)
This study examines digital da’wah practices as an arena for negotiating religious authority through audience interaction on social media. Unlike previous studies that predominantly focus on sermon content analysis, this research highlights how the meaning of da’wah and the legitimacy of preachers are dialogically negotiated within comment sections. Employing a netnographic approach, this study analyzes 45 da’wah contents from three prominent preachers’ accounts Ustaz Hanan Attaki, Gus Baha, and Habib Jafar published between January and June 2024 on Instagram and YouTube. The data were analyzed using qualitative content analysis with thematic coding, focusing on visual narratives and audience comments. The findings reveal three main typologies of audience interaction: (1) theological affirmation that reinforces the symbolic authority of the preacher, (2) trivial fiqh debates indicating the fragmentation of religious authority, and (3) the construction of religious identity through narratives of hijrah and personal morality. These findings demonstrate that digital da’wah functions not merely as a medium for disseminating religious messages but also as a space for the commodification of Islamic symbols and an arena for meaning negotiation between preachers and audiences. This study underscores the importance of understanding digital da’wah as a participatory, commodified form of religious communication that has significant implications for the legitimacy of religious authority in the social media era.